Enhanced sodium and potassium ions storage of soft carbon by a S/O co-doped strategy. (20th January 2021) - Shen, Yuping; Huang, Cong; Li, Yanhua; Zhou, You; Xu, Yali; Zhang, Yan; Hu, Aiping; Tang, Qunli; Song, Xianyin; Jiang, Changzhong; Chen, Xiaohua
Highlights: Defective S/O co-doped soft carbon fabricated by a facile ball mill-thermal treatment strategy. Enhancing the storage capacity without sacrificing the initial coulombic efficiency. Excellent electrochemical property in both sodium and potassium ion batteries. Abstract: The development of soft carbon based anode for sodium and potassium ion batteries (SIBs and PIBs) is hindered by the slow charge storage dynamics due to the larger ionic Na + / K + size. Various strategies, including pore structure regulation and heteroatom doping, have been reported to enhance the batteries performance but sacrificing initial coulombic efficiency. Herein, a simple ball mill-thermal treatment method is developed to prepare S/O co-doped soft carbons (SO-SC) using 3, 4, 9, 10-perylene tetracarboxylic dianhydride (PTCDA) as precursor. The ball-milling process is helpful for the morphology change from small irregular shapes to the large nanoparticle aggregates, which is beneficial for the decrease of electrolyte/electrode contact area, thus enhancing the initial coulombic efficiency (ICE). Besides, the sulfur and oxygen doped sites are introduced into the carbon structure, which enlarge the interlayer distance and increase the Na + or K + coordinate sites. Thanks to these desirable characteristics, the SO-SC for the SIB anode delivers a high ICE of 61.3% and superior rate capability (230.7 mAh g −1 at 2 A g −1 ). A high capacity retention of 86.9% after 4000 cycles is also demonstrated. Furthermore, when applied as PIBs anode, the SO-SC also delivers a high capacity of 412.6 mAh g −1, remarkable rate performance and cyclic performance.